Starting points in critical language pedagogy - Crookes, Graham; Abednia, Arman (Contemporary language education (Greenwich, Conn.), 2021)
Critical language pedagogy, also sometimes referred to as critical ELT, where English is the primary language involved, has a literature in which theoretical and specialized work has outstripped more practically-oriented material. Nevertheless, even practically-oriented publications in this area tend to address the experienced, well-resourced teacher, as opposed to those beginning in this area, or those without much professional support. With a view to helping prepare second language teachers to begin to engage with critical language pedagogy, the authors of this book start from areas of conventional L2 curriculum that teachers naturally use. Each chapter presents material pertinent to areas of language, language teaching and course delivery, starting from a fairly conventional perspective. It then attempts to explain how this conception can be extended drawing upon the ideas of critical (language) pedagogy and teachers' experiences.The authors' experience of working with teachers, who work under different circumstances, in teacher education courses and workshops form key elements of the book. Teachers' voices are also given adequate space so as to provide a comprehensive picture and situated understanding of critical language pedagogy.Dialogical engagement with the initial perspectives of beginning critical language pedagogy teachers who do not necessarily have a fully-worked out "critical philosophy of teaching" or those who wish to practice critical ELT is another feature of the book. Finally, to strengthen the practical orientation of the book, teaching strategies and extracts of materials and lesson plans are also provided.